2021
DOI: 10.1021/acs.energyfuels.1c00494
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Natural Gas Hydrate Exploration and Development in the South China Sea

Abstract: Because of the urgency of energy transition for a net-zero society, the world’s gas demand is rapidly increasing. Natural gas hydrate (NGH) is regarded as the next alternate energy resource to meet the demand, thanks to its high energy density and enormous reserves. As two successful production trials and a series of relevant drilling expeditions were implemented in the northern slope of the South China Sea (SCS), it may now be the most promising district for NGH exploitation in the world. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 147 publications
0
17
0
Order By: Relevance
“…summarizes the natural gas hydrate flow assurance research in China. There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…summarizes the natural gas hydrate flow assurance research in China. There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…20 Lee et al conducted a sequence of laboratory tests on the mechanical characteristics and physical parameters of sediments on the Costa Rican continental margin and found that effective stress and porosity are the main factors influencing their mechanical and physical properties in this region. 21 In recent years, China has successfully conducted two trial productions of NGHs in SCS, 22 providing technical reserves and accumulating valuable experience for the commercial development and utilization of NGHs. This has sparked extensive research by numerous scholars into the mechanical characteristics of hydrate reservoirs in SCS.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, NGH was found in nature and was considered a potential alternative energy source (Makogon, 1965). Subsequently, the United States, Japan, and China have implemented a series of NGH research and development plans (Liu and Li, 2021). More than 230 NGH occurrence areas have been detected in coastal slopes, polar regions, and permafrost zones (Makogon, 2010;Liu and Li, 2021;Wu et al, 2022), with estimated total reserves reaching 3,000-20,000 trillion cubic meters, twice that of traditional fossil fuels (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the United States, Japan, and China have implemented a series of NGH research and development plans (Liu and Li, 2021). More than 230 NGH occurrence areas have been detected in coastal slopes, polar regions, and permafrost zones (Makogon, 2010;Liu and Li, 2021;Wu et al, 2022), with estimated total reserves reaching 3,000-20,000 trillion cubic meters, twice that of traditional fossil fuels (Yin et al, 2019). The total reserves of NGH in China are estimated to be approximately 84 trillion cubic meters; the prospective NGH resources on the northern slope of the South China Sea (SCS) alone amount to tens of billions of tons of oil equivalent (Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%